Low-dose acetylsalicylic acid analog and acetazolamide for prevention of acute mountain sickness : The authors reply - Kayser, B.; Hulsebosch, R.; Bosch, F. (High Altitude Medicine & Biology, 2008)
Basanyat et al. (2008) raise a number of questions about our recent publication on the effects of low-dose carbasalate on acute mountain sickness (AMS) in a high-risk setting (Kayser et al., 2008). In response to the questions the athors have reanalyzed their data and give answers to the questions.